2014
DOI: 10.1261/rna.041566.113
|View full text |Cite
|
Sign up to set email alerts
|

A stem–loop structure directsoskarmRNA to microtubule minus ends

Abstract: mRNA transport coupled with translational control underlies the intracellular localization of many proteins in eukaryotic cells. This is exemplified in Drosophila, where oskar mRNA transport and translation at the posterior pole of the oocyte direct posterior patterning of the embryo. oskar localization is a multistep process. Within the oocyte, a spliced oskar localization element (SOLE) targets oskar mRNA for plus end-directed transport by kinesin-1 to the posterior pole. However, the signals mediating the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(110 citation statements)
references
References 63 publications
3
107
0
Order By: Relevance
“…A possible explanation is that the osk mRNA must be concentrated in the oocyte for at least one aspect of its function. Only the central fragment, within which an oocyte entry signal (OES) has been mapped (Jambor et al 2014), conferred oocyte enrichment. Testing larger fragments, containing the central region and either 5 ′ or 3 ′ flanking sequences, showed that the combination of the central and 5…”
Section: Bru Binding Sites Are Required For Osk Rna Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation is that the osk mRNA must be concentrated in the oocyte for at least one aspect of its function. Only the central fragment, within which an oocyte entry signal (OES) has been mapped (Jambor et al 2014), conferred oocyte enrichment. Testing larger fragments, containing the central region and either 5 ′ or 3 ′ flanking sequences, showed that the combination of the central and 5…”
Section: Bru Binding Sites Are Required For Osk Rna Functionmentioning
confidence: 99%
“…Some of the UAS-egfp transgenes with osk 3 ′ -UTR sequences (Fig. 2) are from Jambor et al (2014). For the new transgenes, the osk 3 ′ -UTR segments used are provided in the Supplemental Materials.…”
Section: Flies and Transgenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly data also suggests that localization-incompetent RNA molecules can hitch-hike on transport particles. [76][77][78] The osk 3 0 UTR mediates hitch-hiking, presumably through RNA-RNA interactions, however the full details of how an RNA is recognized, attached and released from a transport particle is yet to be explained.…”
Section: Active Transport In Early and Mid-oogenesismentioning
confidence: 99%
“…Sequences contributing to the function of this element have been more-precisely mapped to part of a stem-loop structure which resembles the TLS in having an AU-rich stem. Mutation of the distal part of the stem disrupts transport of a reporter mRNA and compensatory changes restore activity, defining the oocyte entry signal (OES) (Jambor et al, 2014). Despite some structural similarity between the TLS and the OES, the OES is depauperate by comparison: it is not active in isolation and directs transport of a reporter mRNA only in the context of larger regions of the osk 3′UTR (Bullock and Ish-Horowicz, 2001;Jambor et al, 2014).…”
Section: Introductionmentioning
confidence: 99%